Nutritional composition and antioxidant potential of Kluai Pakchong KU 46 and Kluai Nam wa Pakchong 50 banana cultivars and properties of their flours - Kunlayanee Suvittawat; Rutai Ruangthamsing; Pimnipa Phengchang; Kwanhatai Tanongjid; Arpathsra Sangnark; Nongnuch Siriwong (Cogent Food & Agriculture)
A comparative analysis of physical characteristics, nutritional composition, bioactive compounds and antioxidant activity of Kluai Pakchong KU 46 (KU-46) and Kluai Nam Wa Pakchong 50 (PC-50) banana cultivars at unripe and ripe stages were conducted. KU-46 bananas contained higher levels of dietary fiber than that of PC-50 at both ripeness stages. The soluble dietary fiber content in KU-46 diminishes with banana ripening, whereas PC-50 shows an increase in soluble dietary fiber during its ripening. Ripe KU-46 banana pulp had high β-carotene, vitamin A, and vitamin C, unlike PC-50. Ripe KU-46 banana pulp had higher calcium levels than unripe, while PC-50 banana pulp exhibited minimal variations in magnesium and calcium contents throughout the ripeness stages. Ripe KU-46 banana pulp exhibited notably higher phenolic content and antioxidant properties. The unripe KU-46 and PC-50 were processed to KU-46 flour (FKU-46) and PC-50 flour (FPC-50) respectively. The elevated phenolic content of FKU-46 enhanced its antioxidant efficacy. Pasting properties revealed that FKU-46 possessed lower pasting temperature, peak viscosity, and breakdown, indicating faster cooking times and increased resistance to heat and shear. The reduced final viscosity and setback values suggested enhanced texture stability in culinary uses. KU-46 banana cultivar demonstrated significant potential in their fresh form and as banana flour for health-conscious consumers.